Anxiety level between mothers of premature-born babies and those of normal-born babies (Chittagong University Journal of Biological Sciences, 2013)
This study was designed to find out the anxiety levels of the mothers in relation to birth status of the babies and anxiety in relation to age of the mothers. The sample consisted mothers of 25 premature born babies and mothers of 25 normal born babies. They were given by the Bengali version of Dutt Personality Inventory to answer. Data were analyzed by t-test, chi-square and product moment correlation. The results revealed that t-ratio (-3.101, df = 48, p